Security Constraint Unit Commitment Considering Line and Unit Contingencies-particle Swarm Optimization - Mohammad Sadegh Javadi (Institute of Advanced Engineering and Science, 2012)
This paper presents a new approach for considering all possible contingencies in short-term power system operation. Based on this new approach, both generator and transmission line outages would be modeled in network-based power system analysis. Multi generator and also parallel transmission lines is modeled in this methodology. We also investigate this claim that feasibility and applicability of this approach is much more than the previous analytical methodologies. Security Constrained Unit commitment (SCUC) program which is carried out by Independent System Operator (ISO), is one of the complex problems which would be handled by this approach. In this paper, a DC-Optimal Power Flow (DCOPF) methodology has been implemented by particle swarm optimization technique. The Lagrangian Relaxation technique is based on the derivatives and the PSO is a non- derivative technique. These approaches are effective tools which can be implemented for short-term and long-term power system analysis, especially for economic analysis of restructured power systems. The DCOPF methodology has been considered for LMP calculation in LR, which is not available in PSO techniques. In the other hand, PSO technique may be able to provide the optimal solution, where LR usually getting stuck at a local optimum in a large scale power system. The simulation results show that the presented methods are both satisfactory and consistent with expectation.